Study on Adenovirus Infection in vitro with Nanoself-Assembling Peptide as Scaffolds for 3D Culture - Ao DS (Dove Medical Press, 2020)
Di-Shu Ao,1,* Lu-Yao Gao,1,* Jing-Han Gu,1 Jun-Hua Qiao,1 Huan Wang,1 Yan-Fei Liu,2 Hong Song1 1Department of Microbiology, School of Basic Medical Sciences, Zunyi Medical University, Zunyi 563000, People’s Republic of China; 2Key Laboratory of Cell Engineering of Guizhou Province, Affiliated Hospital of Zunyi Medical University, Zunyi 563000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan-Fei LiuKey Laboratory of Cell Engineering of Guizhou Province, Affiliated Hospital of Zunyi Medical University, Zunyi, 563000, ChinaTel +86-18286276104Email l_yfei@163.comHong SongDepartment of Microbiology, School of Basic Medical Sciences, Zunyi Medical University, Zunyi 563000, People’s Republic of ChinaTel +86-18985259977Email hongsong@zmu.edu.cnPurpose: To construct a three-dimensional (3D) culture model of adenovirus in vitro using the nanoself-assembling peptide RADA16-I as a 3D cell culture scaffold combined with virology experimental technology to provide a novel research method for virus isolation and culture, pathogenesis research, antiviral drug screening and vaccine preparation.Methods: The nanoself-assembling peptide RADA16-I was used as a 3D scaffold material for 293T cell culture, and adenovirus was cultured in the cells. The growth, morphological characteristics and pathological effects of 3D-cultured 293T cells after adenovirus infection were observed with an inverted microscope and MTS. The proliferation of adenovirus in 293T cells was observed by TEM and detected by qPCR. The levels of TNF-α and IL-8 secreted by adenovirus-infected 293T cells in the RADA16-I 3D culture system were detected by ELISA.Results: The 293T cells grew well in the RADA16-I 3D culture system for a prolonged period of time. The adenovirus infection persisted for a long time with multiple proliferation peaks, which closely resembled those of in vivo infections. The adenovirus virions amplified in the 3D system remained infectious. There were multiple secretion peaks of TNF-α and IL-8 secretion levels in adenovirus-infected 293T cells cultured in 3D culture systems.Conclusion: The nanoself-assembling peptide RADA16-I can be used as a 3D scaffold for adenovirus isolation, culture and research. The 3D culture system shows more realistic in vivo effects than two-dimensional (2D) culture.Keywords: nanoself-assembling peptide, 3D culture, adenovirus, 293T cells